Developing clinical practice guidelines: types of evidence and outcomes; values and economics, synthesis, grading, and presentation and deriving recommendations - Woolf, Steven; Schünemann, Holger J; Eccles, Martin P; Grimshaw, Jeremy M; Shekelle, Paul (Université d'Ottawa | University of Ottawa, 2012)
Abstract Clinical practice guidelines are one of the foundations of efforts to improve healthcare. In 1999, we authored a paper about methods to develop guidelines. Since it was published, the methods of guideline development have progressed both in terms of methods and necessary procedures and the context for guideline development has changed with the emergence of guideline clearinghouses and large scale guideline production organisations (such as the UK National Institute for Health and Clinical Excellence). It therefore seems timely to, in a series of three articles, update and extend our earlier paper. In this second paper, we discuss issues of identifying and synthesizing evidence: deciding what type of evidence and outcomes to include in guidelines; integrating values into a guideline; incorporating economic considerations; synthesis, grading, and presentation of evidence; and moving from evidence to recommendations.